The Effect and Mechanism of Sucrose Consumption to Liver Disease – A Systematic Literature Review - Sim Hellene Anjani Sigma (Biomolecular and Health Science Journal, 2022)
Introduction: One liver disease caused by excessive fat in the liver, called non-alcoholic liver disease (NAFLD), commonly occurs with obesity, diabetes, and other disorders. NAFLD is also associated with hepatic insulin resistance, steatosis, non-alcoholic steatohepatitis (NASH), and cirrhosis. Sucrose consumption has increased recently, and known can promotes NAFLD and will accelerate NAFLD development. This study aimed to discuss the effect and mechanism of sucrose intake on liver disease using a systematic literature review. Methods: The author identified the articles from 6 online search engines, including PubMed, Science Direct, Sinta, Garuda, Google Scholar, and EBSCOHost. A total of 2271 retrieved articles were obtained from combined search strings in Indonesian and English from the search through online search engines. Excluded articles include title not relevant, duplicate articles, not open access, secondary study or review articles, research objective not appropriate, abstract not suitable, and the results/findings not relevant to the aims of this paper. Results: A final of twenty-three articles were retrieved using the Mendeley reference manager. Studies included were published studies, types of experimental and observational studies, and their specific findings of sucrose effects on liver disease. Results reveal that most research was primarily conducted experimentally and in case-control study types on male rats. Conclusion: The most common disease related to sucrose is NAFLD, fibrosis/cirrhosis with the indication of NASH, obesity, insulin resistance (IR), triglycerides (TG), hepatic steatosis, hepatocyte ballooning, and weight gain, which we will discuss further in this review.